Pengembangan Media Pembelajaran Subtema Wujud Benda dan Cirinya Pada Siswa Kelas V Sekolah Dasar - Mahardhika, Irma Rega; , Drs. H. Muhroji, S.E, M.Si.,M.Pd (2017)
This study aimed to describe 1) the stage of development of ICT-based learning media in the form of Powerpoint Interactive refers to the elementary curriculum in 2013 and describes the feasibility of ICT-based learning media in the form of Powerpoint Interactive referring to the SD Curriculum 2013. This study is a research and development (Research and Develompent). Procedure development research used in this study consists of eight steps: a) the initial data collection, b) product planning, c) development of draft product, d) validation expert, e) utility testing, f) forum group discussion (FGD) , g) revision of the design that would become the final product in the form of ICT-based learning media in the form of Powerpoint Interactive referring to the SD 2013 Curriculum for elementary School fifth grade students, h) the dissemination and implementation. 2) Based on the research results developed media in the form of a) ICT based learning media in the form of a Powerpoint Interactive consisting of material, pictures, videos, songs on subjects at Subtheme Form Objects and Characteristics. b) Games in the form of multiple choice questions or a description of evaluation include sound effects applause if answered correctly and sound effects volts if the answer is wrong, the matter can be recycled back if answered questions incorrectly. ICT-based learning media in the form of Interactive Powerpoint feasible to use in learning objects and Characteristics Form subthemes for fifth grade students of the Primary School.